2023
DOI: 10.3390/cancers15061841
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Necrosis Factor Alpha (TNF-α) and Oral Squamous Cell Carcinoma

Abstract: Uncovering the inflammatory mechanisms underpinning initiation, progression, and promotion of oral squamous cell carcinoma (OSCC) development is fundamental to the rational pursuit of targeted therapeutics. Here we present a review of the current knowledge of the role of TNF-α in the aetiology, pathogenesis, and potential therapies with regards to OSCC. TNF-α is worthy of particular attention in OSCC, with its presence demonstrated to enhance cell proliferation and its downregulation demonstrated to inhibit pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 102 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…This study aligns with existing research showing that TNF-α was highly expressed by patients with OSCC. Such an observation emphasizes the contribution that TNF-α may play in promoting oral carcinogenesis [9]. As shown by Brailo et al, patients with oral leukoplakia had significantly higher salivary levels of IL-6 and TNF-α compared to healthy controls [15].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This study aligns with existing research showing that TNF-α was highly expressed by patients with OSCC. Such an observation emphasizes the contribution that TNF-α may play in promoting oral carcinogenesis [9]. As shown by Brailo et al, patients with oral leukoplakia had significantly higher salivary levels of IL-6 and TNF-α compared to healthy controls [15].…”
Section: Discussionmentioning
confidence: 84%
“…TNF-α is of utmost importance due to its involvement in the causation of both OSCC and diabetes of type 2. TNF-α is a main contributor to the interaction among the abovementioned three pathologies [9]. TNF-α is a mediator that could help us understand how it impacts disease development specifically in OSCC among diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, targeting NF-κB activity was thought to be a potential strategy to combat cancer radioresistance [ 30 ]. Recent reports demonstrated that the activation of the TNF-α/NF-κB signaling axis enhances the metastatic capacity and PD-L1 expression of OSCC [ 31 , 32 ]. Inhibition of NF-κB was found to mitigate the cellular invasive ability and restore the responsiveness to radiotherapy in glioblastoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…fibroblast, can produce TNFα [ 40 ]. TNFα has been associated with the progression and prognosis of different cancer types by perturbing several signaling pathways, e.g., Erk1/2 and NF-κB [ 32 ]. Besides, TNFα coordinated with IFNγ to promote MUC16 (CA125) expression in breast and ovarian cancer via the NF-κB signaling axis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral submucosal fibrosis (OSMF) is a disease affecting the oral mucosa, leading to restricted mouth opening and trismus [1]. OSMF is associated with poor oral hygiene and dysphagia and is considered a precursor to squamous cell carcinoma (SCC) [2]. The prevalence of OSMF is higher in the Asia-Pacific region and lower in Europe and the United States.…”
Section: Introductionmentioning
confidence: 99%